Contact strength generating algorithm for application in malaria transmission network - Monday, Eze; Jane, Labadin; Terrin, Lim (2011)
Since malaria transmission emanates from mosquito bites, there must be points of contact between human beings and mosquitoes. Two of such points of contacts in the malaria life cycle are when malaria infected mosquitoes bite uninfected human beings, and when uninfected mosquitoes bite infected human beings. This obviously implies that there is an interaction between human beings and mosquitoes, which scientists can capitalize on to build network models for the study of malaria transmission. Assuming the issues of determination of network structure, and evolution of requisite algorithm for generating realistic network are successfully tackled, an important challenge that must be dealt with is the determination of strength of the relationship between these interacting nodes of the network. The aim of this paper is to tackle the issue of strength of relationship in the transmission network.